Exploring latjeera for its medicinal value - Tyagi, Kavita; Das, Manish (Indian Horticulture, 2019)
The Achyranthes aspera Linn. commonly known as latjeera or apamarga (family Amaranthaceae) is a 1-3 m high, stiff, erect herb, commonly found as a weed throughout India. It is much valued in indigenous medicine. Mainly two varieties are found in India, one is red and another is white. White variety is bitter, pungent, heating, laxative, stomachic, carminative and useful in "vata" and heart disease while red variety is pungent, cooling, emetic, constipating, alexipharmic, useful in ulcers, "vata" and "kapha" and other diseases.